Etika Pedagang Menurut Al-Qur’an Dan Sunnah: Studi Literature - Didik Udayana; Dety Mulyanti (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
The journal entitled "Trader Ethics according to the Qur'an and Sunnah with the author Nahlah et al (2023" contains the profession of a trader who is in great demand by many people. And like other professions, this profession is inseparable from procedures and rules based on government law and sharia based on the Al-Quran and Hadith. This profession is also very noble in the view of Islam, including the eight groups promised by Allah SWT to get the Throne on the Day of Judgment. Besides that, there are many other advantages. Of course, it is accompanied by several conditions that must be met to get this priority, including being honest, straightforward selling, and so on. This study aims to describe ethics in trading as reported in the Al-Quran and Hadith, then synchronized with business ethics according to modern economics. The study uses SLR (Systematic Literature Review) with data sources from the Al Quran, Hadith, and several journals. The results of the study show that the rules or ethics of doing business in a modern economy are also contained in the rules or ethics of trading according to the Al Quran and Hadith. Even more complex than what is in the Al-Quran and Hadith.